Design and Development of a Low-Cost 2.4 GHz GFSK Modulation based Walkie-Talkie - Hashmi, Galib; Huda, Md Nazmul; Mamun, Md Kowsar Hossain; Rahman, Md Habibur (Dhaka University Journal of Applied Science and Engineering, 2023)
A walkie-talkie device can be quite useful in the location where there is no cellphone coverage. Even in the cellphone coverage area it provides communication at very low cost. Currently the law enforcement and military personnel uses frequency modulation (FM) based walkie-talkie systems. The main goal of this research is to design and develop a lowcost walkie-talkie device that can be used by anyone other than the military and law enforcement personals. To construct the walkie-talkie system, the 2.4 GHz industrial, scientific, and medical (ISM) band and GFSK modulation technology have been chosen. In addition, the device includes transceiver module, dc power source, microphone amplifier, audio amplifier, dc-dc booster, and speaker. The coverage range of the implemented walkie-talkie system has been determined and found up to 200 meters. The gadget incorporates a li-ion battery charging system. The voltage, current and power levels at various locations of the device have been measured. It has been found that the maximum operating power consumption is 4.81W and standby power is 1mW. Moreover, the waveforms of different signals at different points of the systems have been observed on the oscilloscope. All of the development process of the system and the performance data are presented in this paper. DUJASE Vol. 7 (2) 16-20, 2022 (July)